2008
DOI: 10.1521/aeap.2008.20.3.249
|View full text |Cite
|
Sign up to set email alerts
|

Peer Norms and Sharing of Injection Paraphernalia among Puerto Rican Injection Drug Users in New York and Puerto Rico

Abstract: This study examines the influence of peer norms on sharing of injection paraphernalia (e.g., indirect sharing behaviors, including sharing of cookers, cotton, rinse water and back/front loading) among Puerto Rican injection drug users (IDUs) in Bayamón, Puerto Rico, and East Harlem, New York City. Data were collected from 873 Puerto Rican IDUs recruited in the two locations by outreach workers. Multiple logistic regression was conducted using sociodemographic and other control variables (e.g., education, frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…While pooling money is frequently associated with higher HIV and HCV risk (Andia et al, 2008; Go et al, 2011), pooling often acts as a way to leverage social capital in times of need (Bourgois et al, 2004). Viewing drug-using behaviors as one aspect of a larger relationship allows researchers to acknowledge traditional proxies such as pooling money for drugs and sex for drugs slightly differently.…”
Section: Discussionmentioning
confidence: 99%
“…While pooling money is frequently associated with higher HIV and HCV risk (Andia et al, 2008; Go et al, 2011), pooling often acts as a way to leverage social capital in times of need (Bourgois et al, 2004). Viewing drug-using behaviors as one aspect of a larger relationship allows researchers to acknowledge traditional proxies such as pooling money for drugs and sex for drugs slightly differently.…”
Section: Discussionmentioning
confidence: 99%
“…The term peer pressure is often used when referring to teen years; however, this influence continues through young adulthood (Clemens, Thombs, Olds, & Gordon, 2008;Perkins, 2007) and perhaps beyond. Among adults, researchers have investigated the impact of peer norms and its influence on drug use and drug-related activities (Andia, Deren, Robles, Kang, & Colon, 2008;Coffin et al, 2007;DaveyRothwell & Latkin, 2007;Longshore, Stein, & Anglin, 1997), and sex (Parsons & Bimbi, 2007;Reece, Milhausen, & Perera, 2006).…”
mentioning
confidence: 99%
“…Since drug use is a highly-stigmatized set of behaviours, it is impossible to create random samples of drug users. Nonetheless, considerable knowledge has been acquired through non-random community samples in studies of drug users and their neighbourhoods by us (Friedman et al, 1989(Friedman et al, , 2007a(Friedman et al, , b, 2008Neaigus, Miller, Friedman, & Des Jarlais, in press;Rossi et al, 2008) and others (Andia, Deren, Robles, Kang, & Colon, 2008;Latkin, Forman, Knowlton, & Sherman, 2003;Latkin & Knowlton, 2005).…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…Other researchers have either adapted these external norms scales (Andia et al, 2008) or used very similar measures in cross-sectional studies. Andia et al found that encouragement to share paraphernalia other than syringes was associated among New York City drug injectors with indirect sharing.…”
Section: Drug Use and Peer Norms In Buenos Aires 555mentioning
confidence: 99%